2021
DOI: 10.3389/fpls.2021.629221
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses and Genomic Predictions of Root Rot Resistance in Common Bean Across Trials and Populations

Abstract: Root rot in common bean is a disease that causes serious damage to grain production, particularly in the upland areas of Eastern and Central Africa where significant losses occur in susceptible bean varieties. Pythium spp. and Fusarium spp. are among the soil pathogens causing the disease. In this study, a panel of 228 lines, named RR for root rot disease, was developed and evaluated in the greenhouse for Pythium myriotylum and in a root rot naturally infected field trial for plant vigor, number of plants germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Optimum ratio of training to testing populations for achieving the highest repeatable predictive ability was 70:30% training:validation for most traits. This level is within the range of what has been found for other studies of genomic prediction in common bean (Keller et al, 2020;Diaz L. M. et al, 2021;Diaz S. et al, 2021;Shi et al, 2021). At 90% training population, the highest average predictabilities as measured by r were achieved, but standard deviations were much larger, leading to less certainty in whether a prediction was accurate.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Optimum ratio of training to testing populations for achieving the highest repeatable predictive ability was 70:30% training:validation for most traits. This level is within the range of what has been found for other studies of genomic prediction in common bean (Keller et al, 2020;Diaz L. M. et al, 2021;Diaz S. et al, 2021;Shi et al, 2021). At 90% training population, the highest average predictabilities as measured by r were achieved, but standard deviations were much larger, leading to less certainty in whether a prediction was accurate.…”
Section: Discussionsupporting
confidence: 86%
“…They found sixteen unique SNP associations in an Andean diversity panel on Pv01, Pv02, Pv03, Pv04, Pv07, Pv08, Pv09, and Pv11, and seven unique SNP associations in a Middle American panel on Pv01, Pv03, Pv04, Pv07, and Pv08 ( Zitnick-Anderson et al, 2020 ). Further GWAS studies have been conducted on root rot caused by Pythium spp., Pythium ultimum , Fusarium oxysporum and Rhizoctonia solani in dry bean ( Oladzad et al, 2019 ; Dramadri et al, 2020 ; Diaz L. M. et al, 2021 ; Paulino et al, 2021 ). With F. solani , the studies listed in Supplementary Table 1 have not found major QTL associated with resistance and the general consensus is that resistance is conditioned by several to many genes with small individual effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are also predominant pathogens that interfere with plant growth by causing damping off and root rot [68]. In African small-scale farms, yield losses of up to 100% caused by the F. solani pathogen in common bean have been reported [69]. In addition, A. euteiches is a soil-borne fungal pathogen that poses a threat to legume production by causing wilting, root rot and consequently yield losses of up to 80% [70,71].…”
Section: Fungal Diseasesmentioning
confidence: 99%
“…In recent years, an increasing number of studies have focused on the GP of common bean. More advanced research mainly focuses on the breeding and development of the common bean, and the construction model of related single nucleotide polymorphisms (SNPs) is determined by combining genome-wide association analysis (GWAS) and GP [ 15 , 16 , 17 , 18 ]. Other studies have mainly focused on the genomic prediction of a few traits in common bean cultivars using different models [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%